Exploring Onomatopoeia Elements Found in Mickey Mouse Adventures Webcomic - Ni Wayan Putri Septiantari; I Dewa Ayu Devi Maharani Santika (Institut Agama Islam Negeri Palopo, 2024)
A webcomic is a series of images sequenced and combined to form a story that can be accessed online. Onomatopoeia is used to build the story and give the comic a more dramatic visual effect. This research aims to explore the onomatopoeia contained in the Mickey Mouse Adventures webcomics edition one. The research method used is descriptive qualitative. The data were collected through observation methods with several stages, such as reading the comics, recording the types of onomatopoeia found, and analyzing the meaning of the onomatopoeia. The theory used to determine the type of onomatopoeia is the theory of Thomas and Clara (2004) while analyzing the meaning of onomatopoeic words is based on the theory of Thomas (1995). The results showed that there are 4 types of onomatopoeia with 66 data found from all types of onomatopoeia in webcomics, including: “sound made by human” with 26 words (39%), “miscellaneous sounds” found 24 words (36%), “calls of animals” 11 words (17%), lastly “sound of nature” for 5 words (8%). The type of onomatopoeia sound made by human beings is the most dominant one used in webcomics. The meaning of onomatopoeia in webcomics is included in abstract and contextual meanings